Ocean acidification compromises a planktic calcifier with implications for global carbon cycling - Catherine V. Davis; Emily B. Rivest; Tessa M. Hill; Brian Gaylord; Ann D. Russell; Eric Sanford (Scientific Reports, 2017)
Abstract Anthropogenically-forced changes in ocean chemistry at both the global and regional scale have the potential to negatively impact calcifying plankton, which play a key role in ecosystem functioning and marine carbon cycling. We cultured a globally important calcifying marine plankter (the foraminifer, Globigerina bulloides) under an ecologically relevant range of seawater pH (7.5 to 8.3 total scale). Multiple metrics of calcification and physiological performance varied with pH. At pH > 8.0, increased calcification occurred without a concomitant rise in respiration rates. However, as pH declined from 8.0 to 7.5, calcification and oxygen consumption both decreased, suggesting a reduced ability to precipitate shell material accompanied by metabolic depression. Repair of spines, important for both buoyancy and feeding, was also reduced at pH < 7.7. The dependence of calcification, respiration, and spine repair on seawater pH suggests that foraminifera will likely be challenged by future ocean conditions. Furthermore, the nature of these effects has the potential to actuate changes in vertical transport of organic and inorganic carbon, perturbing feedbacks to regional and global marine carbon cycling. The biological impacts of seawater pH have additional, important implications for the use of foraminifera as paleoceanographic indicators.